Guns and Suicides. Issue 3 (3rd July 2018) - Cerqueira, Daniel; Coelho, Danilo; Fernandes, Marcelo; Junior, Jony Pinto
ABSTRACT: There is a consensus in the literature that the ratio of suicides committed with guns to total suicides is the best indirect measure of gun ownership. However, such a proxy is not accurate for any locality with low population density in view that suicides are rare events. To circumvent this issue, we exploit the socioeconomic characteristics of the suicide victims in order to come up with a novel proxy for gun ownership. We assess our indicator using suicide micro-data from the Brazilian Ministry of Health between 2000 and 2010.